Examining the Relationship of Emotional Intelligence and Cultural Empathy in Addiction Counselors - Smith, Joshua D. (Journal of addictions & offender counseling, 2020)
The purpose of this study was to examine the relationship between emotional intelligence and cultural empathy in addiction counselors. A hierarchical regression analysis revealed emotional intelligence accounted for most of the variance in cultural empathy in this model.